Investigation of Tongqiao Huashuan Granules’ effect on hippocampal neuron autophagy in vascular dementia rats via the PI3K/Akt-mTOR signaling pathway using network pharmacology and experimental validation - Xiaoqu Jiang; Shuyao Yu; Shuaifeng Yao; Sikai Wang; Jing Cai; Zhongsheng Tang; Shijie Zhu (Frontiers in Neurology)
ObjectiveThis study aimed to apply network pharmacology to identify the active components and key targets of Tongqiao Huashuan Granules in vascular dementia (VaD) and to evaluate its effects on autophagy in hippocampal neurons of VaD rats through animal testing.Materials and methodsThis study first employed network pharmacology (NP) to identify potential components and pathway targets for THg intervention in VaD. A modified two-vessel occlusion (2-VO) method was subsequently analyzed to establish a VaD rat model. Following the interventions, the spatial learning and memory abilities of the rats were assess using a water maze experiment. Morphological and structural changes in neuronal cells within the CA1 region of the rat hippocampus were examined using hematoxylin and eosin (HE) staining. Immunohistochemistry was utilized to assess the proportions of Beclin1-positive and LC3-positive cells in the CA1 region of each rat group, while performed Western blot analysis was conducted to measure protein expression levels of PI3K, p-PI3K, AKT, p-AKT, mTOR, p-mTOR, Beclin1, and LC3 in the hippocampal tissue of the rats.ResultsA total of 76 active components were identified through network pharmacology analysis, with notable components including β-sitosterol, kaempferol, and cinnamophilin. In total, 825 key targets were identified, including IL1B, AKT1, JAK1, and MAPK3. THg and VaD shared 69 common genes. The Gene Ontology (GO) functional enrichment analysis yielded a total of 569 items (BP: 366, CC: 97, MF: 106). KEGG pathway enrichment analysis identified 143 signaling pathways, including TNF, MAPK, AGE-RAGE, and PI3K/Akt pathways. Subsequent validation experiments demonstrated that THg enhanced the learning and memory abilities of VaD rats, improve the morphology of neuronal cells in the CA1 region of the hippocampus, and decreasing the proportion of Beclin1-and LC3-positive cells in this region. Additionally, THg was shown to enhance the expression levels of p-PI3K, p-AKT, and p-mTOR proteins while reducing the expression levels of Beclin1 and LC3 proteins.ConclusionThis study represents the first investigation into the effects of THg intervention in VaD, indicating that its mechanism may involve inhibiting autophagy in hippocampal neurons through activation of the PI3K/Akt-mTOR signaling pathway.